Exploring Tourists’ Interest in Food Heritage Tourism around Yogyakarta Palace - Handayani, Fitri (Gastronomy Tourism Journal, 2025)
The development of gastronomic tourism shows a positive trend as a form of special interest tourism that combines food experiences with cultural and historical values. There is not many study to analyze tourists interest in visiting food heritage sites in Yogyakarta especially in Palace area, and identify their potential as gastronomic tourism attractions.   The method used is descriptive qualitative through in-depth interviews, observation and documentation. The study focused on the Yogyakarta palace area, Ngasem traditional market and Bale Raos Restaurant, involving domestic tourists, traditional food business operators, cultural manager, and stakeholders ini food heritage preservation. The results indicate that the Yogyakarta Palace’s food heritage holds historical and philosophical value, as well as unique falvors and presentation that attract tourists. However, challenges include insufficient digital promotion and competition with modern cuisine. Destination image, food uniqueness, authentic experiences, and emotional engagement are the primary driver of visitor interest. The application of the Nona Helix concept emphasize the importance of collaboration among various stakeholders in the development of gastronomic tourism. The study recommends the preservation of food heritage through the strenghthening of cultural narratives, digital marketing, and innovative presentation methods without compromising traditional values. These finding are expected to support the development of sustainable gastronomic tourism and reinforce Yogyakarta’s cultural identify as a premier destination.